Prospective Life Cycle Assessment at Early Stage of Product Development: Application to Nickel Slag Valorization Into Cement for the Construction Sector - Quéheille, Eva; Dauvergne, Michel; Ventura, Anne (Frontiers in Built Environment, 2021)
Pyrometallurgical nickel industry in New Caledonia produces several tons of slag per year, which is stocked on site. There is no valorization today, except for a small transformation into sand. Pyrometallurgy highly consumes fossil-fuel energy and electricity for ore pre-treatment and nickel extraction inside electrical furnaces, which produces significant CO2 emissions. A new valorization approach is suggested to use these two local productions (slag and CO2) to mineralize slag and produce silico-magnesian cement for the construction sector. In order to ensure suitable environmental performances, many questions arise about the target valorized product: where and how to capture CO2 and produce cement, what constraints should be targeted for the mineralization process, can products be exported and where? Moreover, New Caledonia aims to develop renewable energies for electricity grid, which would mitigate local industries impacts in the future. A prospective Life Cycle Assessment (LCA) is used to define constraints on future product development. Two hundred scenarios are defined and compared as well as electricity grid evolution, using Brightway software. Thirteen scenarios can compete with traditional Portland cement for 12 of the 16 impacts of the ILCD midpoint method. The evolution of electricity grid slightly affects the performance of the scenarios by a mean of less than +/- 25%, bringing a small difference on the number of acceptable scenarios. The main constraint requires improving the mineralization process by considerably reducing electricity consumption of the attrition-leaching operation. To be in line with scenarios concerning carbon neutrality of the cement industry by 2050, a sensitivity analysis provides the maximum energy consumption target for the mineralization process that is 0.9100 kWh/kg of carbonated slag, representing a 70% reduction of the current energy measured at lab scale. Valorization of nickel slag and CO2 should turn to carbon capture and utilization technology, which allows for the production of supplementary cementitious materials, another product for the construction sector. It will be the topic of a next prospective study.